Thank you for the opportunity to help you with your question!

y + 3x = -2

2y + 5x = 15

the second step you multiply the 1st equation by 5 and the second equation by 3 and subtract the 1st equation from the second equation

(y + 3x = -2) 5

(2y + 5x = 15)3

you get

(5y+15x=-10) - (6y + 15x = 45)

-y=-55 therefore, y= 55

find x

y + 3x = -2 and y=55

55 + 3x = -2

3x = -57

x=-19

y=55

ans (x,y) = (55, -19)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up